The Tale and Tell of the Retired Teachers’ Philosophies - Danganan, Catherine; Gamboa, Alberto; Koh, Aileen (Future Science / FSH-PH Publications, 2022)
This is qualitative research which utilized the narratology, intended to understand the philosophies of retired teachers from a state university in Pampanga, as they tell their lived experiences. Six (6) retired teachers participated in the pursuance of the study. The researchers used purposive sampling. To obtain pertinent information, the participants must be a retired teacher from a university. The retired teacher must be sixty- sixty-five (60-65) years old and has rendered fifteen (15) years or more in the university and active members of the community as they are still engaged in public and private organizations. The used instrument was a semi-structured questionnaire that was content validated prior to its utilization. Data were analyzed using the six (6) phases of Braun and Clarke’s Thematic analysis. The philosophies of the retired teachers are focused on their experiences, which brought significant mark in their lives as teachers. Therefore, it is recommended to recognize the contributions of the retired teachers by initiating programs which are holistic in nature such as fellowship, socializations or honorary celebrations.